2004
DOI: 10.1073/pnas.0404379101
|View full text |Cite
|
Sign up to set email alerts
|

Gestational exposure of Ahr and Arnt hypomorphs to dioxin rescues vascular development

Abstract: The aryl hydrocarbon receptor (AHR) is commonly known for its role in the adaptive metabolism of xenobiotics and in the toxic events that follow exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin (dioxin). Previously, we have demonstrated that the AHR and its heterodimeric partner, the AHR nuclear translocator (ARNT), play a role in the developmental closure of a hepatic vascular shunt known as the ductus venosus (DV). To investigate the mechanism of DV closure, we generated hypomorphic alleles of the Ahr and Arn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
93
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 22 publications
3
93
1
Order By: Relevance
“…The conditional Ahr allele (Ahr fx ) contains exon 2 of Ahr flanked by loxP sites (''floxed'') for later excision by a cell-specific Cre recombinase (Cre). The Ahr fx mice were generated from the Ahr fxneo allele (8). Mice homozygous for the Ahr fxneo allele were crossed to a transgenic line carrying Cre under the control of the Ella promoter (Cre Ella , strain name: FVB͞N-Tg(EIIa-cre)C5379Lmgd͞J) (The Jackson Laboratory) to generate partial recombinants and obtain the conditional Ahr fx allele lacking the neomycin gene (11,12).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The conditional Ahr allele (Ahr fx ) contains exon 2 of Ahr flanked by loxP sites (''floxed'') for later excision by a cell-specific Cre recombinase (Cre). The Ahr fx mice were generated from the Ahr fxneo allele (8). Mice homozygous for the Ahr fxneo allele were crossed to a transgenic line carrying Cre under the control of the Ella promoter (Cre Ella , strain name: FVB͞N-Tg(EIIa-cre)C5379Lmgd͞J) (The Jackson Laboratory) to generate partial recombinants and obtain the conditional Ahr fx allele lacking the neomycin gene (11,12).…”
Section: Methodsmentioning
confidence: 99%
“…Mice homozygous for the Ahr fxneo allele were crossed to a transgenic line carrying Cre under the control of the Ella promoter (Cre Ella , strain name: FVB͞N-Tg(EIIa-cre)C5379Lmgd͞J) (The Jackson Laboratory) to generate partial recombinants and obtain the conditional Ahr fx allele lacking the neomycin gene (11,12). Discrimination between the WT and floxed allele was accomplished by PCR amplification of the region surrounding the loxP site located 3Ј to exon 2, as described (8). Excision of the neomycin gene was detected by Southern blot analysis of BglIIdigested genomic DNA by using a 500-bp probe specific to exon 2 of Ahr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include a patent ductus venosus (DV), persistent hyaloid arteries in the eye, decreased hepatic perfusion, a confused vascularization in the corneal limbus, and cardiac hypertrophy (4-6). Experiments using Ahr and Arnt hypomorphic mice have demonstrated that, similar to its role in xenobiotic metabolism, the developmental role of AHR requires activation of the receptor and formation of an AHR/ARNT dimer complex (7,8). Additionally, experiments using tissue-specific AHR null mice have demonstrated that AHR expression within endothelial and/or hematopoietic cells is necessary for closure of the DV (9).…”
mentioning
confidence: 99%